TINJAUAN SISTEMATIS PENGELOLAAN OBAT DI BERBAGAI FASILITAS KESEHATAN INDONESIA: SEBUAH REVIEW ARTIKEL - Nusantara, Julius; Sutjiatmo, Afifah B (Jurnal Buana Farma, 2025)
This study aims to analyze drug management in various healthcare facilities in Indonesia, including hospitals, primary healthcare centers (puskesmas), and other health institutions. The primary focus is on the implementation of policies and drug management practices, as well as the role of healthcare professionals, particularly pharmacists, in ensuring drug availability in accordance with the National Formulary and pharmaceutical service standards. This study employs a review article approach with a descriptive-analytic method and qualitative analysis, reviewing 40 relevant journals obtained from databases such as PubMed, Google Scholar, and Sinta. The findings indicate that 90% of the reviewed journals report suboptimal drug management, with major challenges including drug unavailability, price fluctuations, and weaknesses in drug management systems. Therefore, this study recommends enhancing training for healthcare professionals, optimizing resource allocation, and developing a more efficient drug management information system to improve drug availability and efficiency in Indonesian healthcare facilities.